Terminal velocity of crambe’s fruit and seeds in moisture content function (Research, Society and Development, 2020)
During the processing steps and storage of agricultural products is common to use fluids as a means of transport and separation of impurities present in the grain mass, thus, it is necessary to know the aerodynamic characteristics, mainly related to grain and seeds. By determining the terminal velocity it is possible to perform the cleaner, transporter and dryer machine’s adjustment and operation and cleaning machines, transport and drying. This study aimed to determine the experimental terminal velocity and calculated for crambe’s (FMS Brilhante cultivars) fruit and seed, due to different moistures contents. The experiment was conducted in a completely randomized design in a factorial arrangement 2 x 9 (fruits and seeds x moisture contents 0.250; 0.220; 0.190; 0.163; 0.136; 0.111; 0.087; 0.064 and 0.042 dry basis - d.b.), in four replicates. For the experimental determination utilized a gram of sample product in an experimental equipment of the air column consists of a centrifugal fan connected to a transparent acrylic tube. The moisture content of the fruit and crambe seed affects the values of terminal velocity. The terminal velocity of fruit and crambe seed decreases with the reduction of the product’s moisture content. The calculated terminal velocity is less than the experimental one.